2002
DOI: 10.1097/00007890-200204270-00005
|View full text |Cite
|
Sign up to set email alerts
|

Successful extracorporeal porcine liver perfusion for 72 hr1

Abstract: It is possible to maintain a liver in a viable condition for a minimum of 72 hr of extracorporeal perfusion. This technique has been developed primarily as a preclinical model of extracorporeal liver support with the intention of proceeding to a clinical trial in patients with fulminant liver failure. However, it also has potential applications in organ preservation or resuscitation before transplantation and in the experimental study of isolated liver physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(166 citation statements)
references
References 28 publications
11
155
0
Order By: Relevance
“…Numerous studies have demonstrated the advantage of NMP over CS in the preservation of DCD livers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), suggesting that NMP may greatly benefit the practice of liver transplantation. conducted using whole blood (WB) (9)(10)(11)(19)(20)(21). The same group recently introduced NMP in human liver transplantation using blood and additives during perfusion (18).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the advantage of NMP over CS in the preservation of DCD livers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), suggesting that NMP may greatly benefit the practice of liver transplantation. conducted using whole blood (WB) (9)(10)(11)(19)(20)(21). The same group recently introduced NMP in human liver transplantation using blood and additives during perfusion (18).…”
Section: Introductionmentioning
confidence: 99%
“…Perfusate reservoirs may be gassed using glassware with a sintered glass filter (Tindal, 1957), with a bubble oxygenator, which bubbles (pure) oxygen through the blood reservoir (Smith et al, 1985), or by using a rotating disc oxygenator Cameron et al, 1972), whereby several parallel discs rotate within the reservoir containing unoxygenated blood and the gas exchange occurs at the disc-blood interface. More recently, the use of membrane or hollow fiber oxygenators (Butler et al, 2002;Müller et al, 2013) typically deployed during CPB surgery or life support (extracorporeal membrane oxygenation) has been reported in perfusion experiments. These systems generally follow the same concept as rotating disc oxygenators, as oxygen exchange occurs at a porous membrane.…”
Section: Perfusatementioning
confidence: 99%
“…Instead of autologous blood perfusions, several experiments have utilized homologous blood or blood components with no apparent negative effects (Hebb and Linzell, 1951;Cameron et al, 1972;Butler et al, 2002). While this may simplify the experimental set-up and potentially reduce inter-animal variability, it is plausible that incompatibility reactions can occur, thereby affecting outcome variables.…”
Section: Perfusatementioning
confidence: 99%
See 2 more Smart Citations